Lithuanian Postcard in the struggle against Imperial Russia - Kaunas, Domas (Knygotyra, 2022)
The article is devoted to a peculiar episode of the struggle of Lithuanians against the policy of persecution based on nationality which was pursued by Imperial Russia between 1864 and 1904. Its participants were representatives of the parts of the Lithuanian nation separated by the border between Germany and the Russian Empire – Martynas Jankus (1858–1946), a German citizen, a Lithuanian of East Prussia, the owner of a printing office in Tilsit (Lith. Tilžė, currently Sovetsk, a town in Kaliningrad Oblast, the Russian Federation) and a group of Lithuanian young people who were operating illegally, a group of citizens of the Russian Empire. The time under discussion is the 1890s. During that period, the Lithuanian national movement was rapidly developing and strengthening while striving to bring together both parts of the nation and the USA-based Lithuanian diaspora community. One of the most important measures of the common struggle was the distribution of publications printed in Latin characters in the Lithuanian language which were banned to be published in the territory of Russia but were legally printed in East Prussia and smuggled across the border into Lithuania. From there, the publications were sent to Lithuanian communities all over the Russian Empire. This struggle resulted in victory: the ban was lifted by Order of the Cabinet of Ministers of Russia issued in 1904.To strengthen the political opposition, Lithuanian intellectuals printed not only books, brochures and newspapers but also various minor publications – political leaflets. Students of Russian universities and Lithuanian intellectuals graduates of these higher education institutions prepared texts and sent funds intended for their publication to the printing offices of Lithuanians and Germans in East Prussia. The number of such leaflets surviving to the present day is very small. One of these publications was an anonymous card of the size of a standard German postcard (95 x 140 mm). Thus far, three of them have been found in Lithuanian libraries and archives, and one has been discovered in the National Library of Russia in Saint Petersburg. A composition of two illustrations is printed on one side of the card: a Lithuanian countrywoman and a Cossack standing in front of her with a raised whip and a bottle of vodka as a gift for obedience. This symbolised a spread of orthodoxy and the deportation of Lithuanians from their native land. The following exclamation of the Cossack is printed: Are you a Lithuanian? Go to Russia! The explanation of the content of the illustration and the encouragement (first of all, to Catholic believers) to oppose the plans of the authorities are printed in small characters. They are related to the colonisation of Siberia. The statements are well-grounded, the exposition of the subject is logical and written in the correct Lithuanian language. Most probably, it was created by the graduate of the Faculty of Law of the University of Moscow Vladas Mačys (1867–1936).Vaclovas Biržiška, Professor of Law at the University of Lithuania in Kaunas and Director of the University Library, was the first to describe this publication bibliographically. The author regarded this publication as a postcard, attributed it to Martynas Jankus’ printing office and dated it ‘1892’. A more precise description was publicised in the fundamental work of Lithuanian national bibliography Lietuvos TSR bibliografija. Serija A: Knygos lietuvių kalba (Bibliography of the Lithuanian SSR. Series A: Books in the Lithuanian Language; vol. 2: 1862–1904. Book 2 (Vilnius, 1988, p. 401, No. 4065). It was compiled in the Soviet era, and the only available copy stored in Mikhail J. Saltykov-Shchedrin State Public Library (currently renamed the Russian National Library in Sankt Petersburg) served as the basis for it. The present author amended the publication date of the postcard (1891) and specified the circumstances of its distribution, while also ascertaining that the artist of the illustrations was the lithographer of Tilsit Johann Mai.
Keywords: Ban on publishing Lithuanian books in the Latin alphabet imposed by the Imperial Russian Government between 1864 and 1904; resistance of the Lithuanian National Movement; illegal publication of political leaflets; Lithuanian publications in the form of a postcard; Lithuanian students of Russia; lawyer Vladas Mačys; book publisher and printer Martynas Jankus; lithographer of Tilsit Johann Mai